An Investigation of Self-determination Factors among Postgraduate Students - Rahmat, Noor Hanim (American Journal of Education and Learning, 2019)
The influx of adult students furthering their studies in universities as postgraduate learners have created more issues on learning and learners. Learning has taken many forms- full-time, part-time, online, distance learning and many more. Learners can be fresh school leavers or even working adult adults. Learners can be pursuing certificates, diploma, bachelor degree or even postgraduate studies. There are also studies conducted to understand self-determination factors of these learners. This qualitative explores the pushing factors that influence students to embark on postgraduate studies. This study also looks into factors that retain as well as demotivate the students in the study programme. A purposive sample of nineteen students narrated their first-semester learning experience in log entries. Data from the entries were analysed and coded to reveal pushing, retaining as well as demotivating factors among postgraduate adult learners. Results of the findings have an interesting implication on demotivational factors of adult, postgraduate learners.